2014
DOI: 10.1111/1365-2664.12299
|View full text |Cite
|
Sign up to set email alerts
|

Flower‐visiting insects and their potential impact on transgene flow in rice

Abstract: Summary1. Rice is one of the most important crops in the world. Several transgenic varieties of rice have been developed, and some have recently entered pre-production trials. One concern with genetically modified (GM) crops is transgene escape, but prior studies suggest this risk is low for rice because it is self-pollinated and the dispersal of pollen by wind is limited. 2. Little is known about the impact of pollen transport by insects. We characterized the insects visiting rice plants during anthesis and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…Apis mellifera has also been selected as surrogate species in nontarget risk assessments of insect-resistant, genetically engineered plants [5,[8][9][10] because honey bees consume pollen [11][12][13] and because the pollen produced by most insect-resistant, genetically engineered plants contains insecticidal Cry proteins. The honey bee has previously been used to assess the nontarget effects of Bt cotton [14][15][16][17] and maize [18][19][20], but it has rarely been used for Bt rice [8], although many studies have demonstrated that honey bees collect rice pollen as a food source during rice anthesis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Apis mellifera has also been selected as surrogate species in nontarget risk assessments of insect-resistant, genetically engineered plants [5,[8][9][10] because honey bees consume pollen [11][12][13] and because the pollen produced by most insect-resistant, genetically engineered plants contains insecticidal Cry proteins. The honey bee has previously been used to assess the nontarget effects of Bt cotton [14][15][16][17] and maize [18][19][20], but it has rarely been used for Bt rice [8], although many studies have demonstrated that honey bees collect rice pollen as a food source during rice anthesis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Pu et al. () also reported insect‐mediated pollination in rice, where increased frequency of transgene flow was detected.…”
Section: Gene Flow: From Cultivated To Weedy Ricementioning
confidence: 98%
“…This has been largely due to continuing debate over their potential long-term effects and difficulties in managing adaptation by target organisms, particularly in tropical regions where cropping is more intensive (Sudianto et al, 2013;Pu et al, 2014) and in developing nations where farms are small (usually >2 ha) and where area-wide resistance management would be consequently difficult (Teetes, 1994).…”
Section: Barriers and Trapsmentioning
confidence: 99%